Vibration control of adjacent beams with pneumatic granular coupler: An experimental study. (December 2016) - Bajkowski, Jacek Mateusz; Bajer, Czesław; Dyniewicz, Bartłomiej; Pisarski, Dominik
Abstract : Highlights: Vibration abatement of adjacent structures can be improved by active coupling. Coupler filled with granular material and controlled with underpressure is used. High efficiency of designed control is validated experimentally. The device and the obtained control law are practical for implementation. Abstract: A novel type of pneumatic device filled with granular material is proposed in the implementation of a switched control strategy to stabilize the vibration of slender structures. The analytically obtained control law for the airtight, elastic, granular coupler is implemented in a test structure with a relay-type control logic. In the experiment, the deformable granular coupler semi-actively damps an initially deflected pair of adjacent, aluminum beams. Two cases of initial excitation are considered, showing an improvement of up to 33% in vibration abatement efficiency compared to the passive case. Although this semi-active device is conceptually simple, its ease of operation and low cost should attract the attention of engineers who seek solutions that can be used to build new structures and upgrade existing ones.